2003
DOI: 10.1002/jcc.10272
|View full text |Cite
|
Sign up to set email alerts
|

New analytic approximation to the standard molecular volume definition and its application to generalized Born calculations

Abstract: In a recent article (Lee, M. S.; Salsbury, F. R. Jr.; Brooks, C. L., III. J Chem Phys 2002, 116, 10606), we demonstrated that generalized Born (GB) theory provides a good approximation to Poisson electrostatic solvation energy calculations if one uses the same definitions of molecular volume for each. In this work, we present a new and improved analytic method for reproducing the Lee-Richards molecular volume, which is the most common volume definition for Poisson calculations. Overall, 1% errors are achieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
678
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 473 publications
(684 citation statements)
references
References 27 publications
6
678
0
Order By: Relevance
“…28 The resulting dielectric profile (z) for dipalmitoylphosphatidylcholine (DPPC) bilayers is shown in Figure 1. The HDGB model is based on the GBMV model, 26 a generalized Born (GB) version that utilizes the standard molecular volume and can predict the electrostatic solvation free energy very accurately when compared with Poisson theory. 26 In the GBMV formalism, the effective Born radius R is determined according to the Coulomb Field approximation including a correction term.…”
Section: Hdgb Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…28 The resulting dielectric profile (z) for dipalmitoylphosphatidylcholine (DPPC) bilayers is shown in Figure 1. The HDGB model is based on the GBMV model, 26 a generalized Born (GB) version that utilizes the standard molecular volume and can predict the electrostatic solvation free energy very accurately when compared with Poisson theory. 26 In the GBMV formalism, the effective Born radius R is determined according to the Coulomb Field approximation including a correction term.…”
Section: Hdgb Modelmentioning
confidence: 99%
“…45 As of this writing, only 1 simulation study was reported using a united-atom force field. 46 In addition to simulations with the HDGB model, simulations of all 3 proteins were also performed in a homogeneous implicit aqueous environment using the standard GBMV model 26 for comparison with the HDGB model.…”
Section: Hdgb Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The original parametrization determined for the GBMV2-S 20 model maximizes the agreement with Poisson theory. 11,12 Of the two GBMV2 models tested, GBMV2-S 10 exhibited the lowest T c of 389 K. Nevertheless, the predicted T c is higher than experimental observations. Depending on the sequence variant of the SH3 domain and experimental pH conditions, the reported melting temperature is roughly 340 K. 24 Although the deviation between the experimental temperature and our calculation is less drastic than that observed in the work of Pitera and Swope on modeling the Trp-cage, 21 where they predicted a T c value nearly 85 K higher than the experimental determination, both studies indicate that REMD simulations with GB models tend to overstabilize native structures.…”
Section: Discussionmentioning
confidence: 89%
“…10 The numerical stability of the GBSW model is well suited for MD simulations of proteins, although the dielectric boundary is fundamentally different from the molecular surface in its treatment of the interstitial space between atoms. A truer mimic of the molecular surface is given by the GBMV2 solvent model, 11,12 where an analytical formulation is used to build a molecular volume based on superposition of spherical functions.…”
Section: Introductionmentioning
confidence: 99%